Pembuatan Content Management System Website Pengajuan Kegiatan Organisasi Menggunakan Framework Express Js Dan React Js - Renzha, Abraham; Marna Putra, Zagita; Achmad, Andita Dani (Prodi Sistem Informasi UIN Alauddin, 2025)
Fajar University's (UNIFA) adoption of contemporary technology demonstrates the necessity of an improved digital information system for the administration of student activities. Workflows that are now done by hand are laborious and prone to errors. The purpose of this research,